Accurate Modeling Simulation and Experimental Study of Hybrid Multi-Terminal UHVDC Transmission System - Xing, Chao; Cai, Wang; Che, Yanbo; Bi, Guihong; Chen, Shilong; Gao, Jingye; Wang, Long (Frontiers in Energy Research, 2022)
This paper researches on the Wudongde hybrid multi-terminal UHVDC transmission project (referred as Wudongde transmission project in short), and establishes an accurate simulation model of the hybrid multi-terminal UHVDC transmission system with the electromagnetic transient simulation software PSCAD/EMTDC. The primary system is divided into three modules: AC system, converter station and transmission line, and the detailed simulation model of each module’s primary system is established according to the actual project parameters; based on the LCC-HVDC and MMC-HVDC control systems in the CIGRE standard test system, the standard control system is modified accordingly according to the characteristics of the LCC-HVDC and MMC-HVDC control systems, and a simulation model of the control system applicable to the hybrid multi-terminal UHVDC transmission system is established; the primary system and the control system are combined to form an accurate simulation model of the hybrid multi-terminal UHVDC transmission system. The accuracy and credibility of the model is verified through the comparation of the recording waveform and the simulating waveform of steady-state and transient operation. The simulating and field recording waveforms show that the model can simulate the Wudongde transmission project accurately and can be used as an effective tool for the further study of the electromagnetic transient characteristics of the hybrid multi-terminal UHVDC transmission system.